An overview on multi-ingredient memory enhancers and Anti-Alzheimer's formulations from Traditional Persian Pharmacy - Farid Dabaghian; Amir Azadi; Mahnaz Setooni; Mohammad M. Zarshenas (Shiraz University of Medical Sciences, 2017)
Dementia and Alzheimer's, the common cause of this syndrome, have been given special considerations to be managed by natural medicaments. Parallel to conventional medications for dementia and Alzheimer, there are various remedies in pharmaceutical manuscripts of Persian medicine. This review provides various compound formulations to manage and control the sign, symptoms and complications of memory loss, Alzheimer's and allied disorders. These remedies have been cited in a series of traditional pharmaceutical manuscripts of Persian medicine, namely Qarābādin or prescription. With a view to the positive pharmacological or biological activities of the constituents of filtered formulations, many of those can be reformulated, and either experimentally or clinically evaluated in order to be introduced as new natural remedies in this field.